Pathology of HPV-Associated Head and Neck Carcinomas: Recent Data and Perspectives for the Development of Specific Tumor Markers - Sastre-Garau, Xavier; Harlé, Alexandre (Frontiers in Oncology, 2020)
A significant subset of carcinomas developed in the head and neck (H&NCs) are associated with specific human papillomaviruses (HPV) genotypes. In particular, 40-60% of oropharyngeal carcinoma cases are linked to HPV. Epidemiological studies have demonstrated that HPV oral infections are predominantly sexually transmitted and are more frequent among men (10-18%) than women (3.6-8.8%). Although there is a large diversity of HPV genotypes associated with H&NCs, HPV16 lineage represents 83% of the reported cases. The prognostic value of HPV as a biological parameter is well recognized. However, the use of HPV DNA as a diagnostic and/or predictive marker is not fully developed. Recent data reporting the physical state of the HPV genome in tumors have shown that HPV DNA integration into the tumor cell genome could lead to the alteration of cellular genes implicated in oncogenesis. Most importantly, HPV DNA corresponds to a tumor marker that can be detected in the blood of patients. Profile of the HPV DNA molecular patterns in tumor cells using New Genome Sequencing-based technologies, allows the identification of highly specific tumor markers valuable for the development of innovative diagnostic and therapeutic approaches. This review will summarize recent epidemiological data concerning HPV-associated H&NCs, the genomic characterization of these tumors, including the presence of HPV DNA in tumor cells, and will propose perspectives for developing improved care of patients with HPV-associated H&NCs, based on the use of viral sequences as personnalized tumor markers and, over the longer term, as a therapeutic target.